Developing a framework for transdisciplinary communication in multifaceted agricultural research organisations - Mumuni, Eliasu (2018)
Agriculture represents a class or expression of complexity which researchers need to look at because of its immense contribution to rural development and poverty reduction. Scientists and researchers per their disciplinary training and specialisations differ in wider perspectives and methodologies. In addition to the compartment functioning processes of organisations, fluid interaction and collaboration of actors are further limited. This study examines how actors in Crops for the Future (CFF) interacted formally and informally as a complex agricultural research organisation to address the transdisciplinary communication challenges it faces. Using ethnographic methods with participant observation, interviews and official document reviews, the study revealed that, the structuring of CFF into themes and programmes was intended to network and work in their areas of disciplines. The study revealed that internal policies of CFF such as the research value chain (RVC), the doctoral support programmes (DTP) and flagship projects aim to improve research collaboration and as a research strategy, tend to support working together effectively. However, it further revealed that, though actors collaborate and network across different knowledge communities, elements of personal interest and power appear to play a significant role in that drive. Raising questions of communication and reporting process, revealed a mixed form of vertical and horizontal hierarchies, supported by a project and functional structures of management in CFF. The informal practices of actors in CFF (social networking, friendship, interactions etc.) tend to strongly support and enhance the formal structures and policies (programmes, themes, reporting and management structure etc.).